The Effects of the Form of Sugar (Solid vs. Beverage) on Body Weight and Neuronal Activity: A 28 Day Randomized Pilot Study (P08-001-19). (24th October 2019) - Apolzan, John; Carmichael, Owen; Fearnbach, S Nicole; Kirby, Krystal; Ramakrishnapillai, Sreekrishna; Beyl, Robbie; Gadde, Kishore; Collier, J Jason; Martin, Corby
Abstract: Objectives: To test if sugar sweetened beverages (SSBs) and sugar sweetened solids (SSSs) have differential effects on body weight and food reward processing. Methods: In a single blind RCT, twenty participants with a BMI between 20–40 kg/m 2 were randomized to consume a 20 fl oz soda/d (SSB, 248 kcal) vs. the equivalent energy and nutrients in solid form (SSS; similar to a thick jello and/or gummy candy). At baseline and day 28, fasting body weight and fed state brain activation responses to low fat high sugar foods (LF < 30%, HS > 30%) and non-food objects were assessed. The fMRI scan began 30 min after initiation of consumption of the 248 kcal dose of their randomized treatment. Summary measures of differences in fMRI BOLD signals between LFHS vs non-food images were calculated in a set of a priori defined brain regions implicated in energy homeostasis, taste, reward, and motivation to eat. Results: Ten participants in the SSB (6F 4 M; 80% White; 39 ±4 y, Mean ± SEM) and ten in the SSS (3F 7 M; 60% White; 36 ± 5) completed the study. Baseline BMI was 28.2 ± 1.7 kg/m 2 and 26.3 ± 1.4 in the SSB and SSS groups, respectively. No difference in change in body weight for SSB vs. SSS (0.56 ± 0.43 kg; P = 0.22) was seen. Changes in fMRI activation in homeostatic and taste regions were not different. Among reward and motivation related regions, fMRI activation within the caudate nucleus, cingulate gyrus, and medial orbitofrontal cortex were not different at baseline, but increased in SSS and decreased in SSB group (mean group differences in activation change: –0.30 ± 0.15, –0.36 ± 0.11, and –0.60 ± 0.25, P ˂ 0.05; respectively). fMRI activation in the insula was greater at baseline in SSS compared to SSB but the two groups converged to similar values at day 28 (mean group differences in activation change: 0.19 ± 0.08, P ˂ 0.05). Conclusions: Consumption of SSB vs. SSS products produced distinct changes to brain activity within specific brain regions that control eating behavior despite no change in body weight between groups. Understanding the neural and physiological consequences of consuming added sugar in different forms will better inform current efforts to reduce its consumption and help regulate policy. This pilot study provides promising data for a longer duration, well-powered follow-up study. Funding Sources: NIH U54GM104940, P30DK072476, Pennington Biomedical Research Foundation.